Analisis Perlakuan Dana Non Halal sebagai Dana Kebajikan dan Reputasi Pada Lembaga Keuangan Syariah - Mutaqin, Kikin; Abdul Hakim, Atang; Nurwahidah, Dede (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2024)
This study aims to analyze the implementation of the treatment of non-halal funds including aspects of legal rules as a benevolent fund and see its correlation to the reputation of Islamic financial institutions. This research uses the library research method with data collection techniques through searching library references, in the form of books, journals and other scientific publications. Data analysis is carried out in depth on the meaning contained in each concept and paradigm both from verses in the Qur'an, Hadith, and the opinions of the figures. The results of this study explain that non-halal funds are a segment that requires in-depth study, because at first it did not have a legal basis in its management, only limited to the presentation and recording of the accounting side. The role of the ulama through the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) which issued fatwa Number 123 of 2018 is the basis for the treatment and legal status of non-halal funds. In addition, non-halal funds have an indirect effect on the reputation of Islamic financial institutions, meaning that the higher the receipt of non-halal funds, the worse the reputation of the institution.